Social media, s-commerce and social capital: a netnography of football fans and organisations. (16th March 2023) - Fenton, Alex; Procter, Chris; McLean, Rachel; Quan-Haase, Anabel
Social media channels allow brands to establish meaningful social relations with customers. This paper evaluates the role of social capital in building these online relationships for the benefit of commercial value and s-commerce for brands. Extensive empirical data was collected over a two-year netnography study using the social media channels of a football club in the UK as a vehicle for the study. A blended methods netnography (Fenton and Procter, 2019) was employed that included online participant observation, social network analysis, and semi-structured interviews with football fans and social media managers. The majority of brand social media followers are often found to be lurkers. These are weakly connected, social media followers - listening but not interacting. Finding ways to strengthen social capital with social media followers have significant brand and commercial implications. Positive interactions are critical to building social capital to strengthen and sustain the brand. Social capital can be successfully built and nurtured through engaging content and positive interactions through social media channels.